2009
DOI: 10.1016/j.intimp.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A robust in vitro screening assay to identify NF-κB inhibitors for inflammatory muscle diseases

Abstract: Specific therapies are not available for inflammatory muscle diseases. We and others have shown that the pro-inflammatory NF-κB pathway is highly activated in these conditions. Since NF-κB is an important therapeutic target, we decided to utilize an in vitro screening assay to identify potential inhibitors that block TNF-α induced NF-κB activation in a C2C12 muscle line that stably expresses an NF-κB luciferase reporter gene. We have tested multiple potential anti-inflammatory agents in undifferentiated myobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Celastrol has been shown to suppress IκB phosphorylation and NF-κB activation by inhibiting TAK1 activation (17). We have previously developed a muscle-based NF-κB inhibitor screening assay and shown that celastrol is one of the powerful inhibitors of NF-κB under this system (18). Based on this data, inhibition of NF-κB anti-inflammatory agents such as celastrol to suppress immune activation in dysferlin-deficient muscle could ameliorate the disease pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Celastrol has been shown to suppress IκB phosphorylation and NF-κB activation by inhibiting TAK1 activation (17). We have previously developed a muscle-based NF-κB inhibitor screening assay and shown that celastrol is one of the powerful inhibitors of NF-κB under this system (18). Based on this data, inhibition of NF-κB anti-inflammatory agents such as celastrol to suppress immune activation in dysferlin-deficient muscle could ameliorate the disease pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro drug screening assay for NF-B inhibition in C 2 C 12 cells was done as described previously (Baudy et al, 2009). To measure the ablation of NF-B effects by the addition of a GR antagonist, reporter cells were pretreated for 1 h with the drug at a constant concentration and 17␤-hydroxy-11␤-[4-dimethylamino phenyl]-17␣-[1-propynyl]estra-4,9-dien-3-one (RU-486) at increasing concentrations (1 nM to 10 M).…”
Section: Nf-b Inhibitionmentioning
confidence: 99%
“…Force measurements were conducted on the extensor digitorum longus muscle of the right hindlimb of the mdx mouse as described previously (Spurney et al, 2011). Dissociative ⌬-9,11 Steroids and studied drug effects on both undifferentiated myoblasts and multinucleated myotubes (Baudy et al, 2009). We synthesized anecortave, and the 21-hydroxy desacetate form, VBP1 ( Fig.…”
Section: Baudy Et Almentioning
confidence: 99%
“…This protein-protein complex inhibits the activity of a large number of pro-inflammatory transcription factors, including NFjB, without binding to DNA [7]. Decreased transcription of NFjB results in decreased production of several pathogenic cytokines and chemokines [8][9][10]. Another mechanism of GC activity, known as transactivation, occurs when the GR-steroid complex forms a homodimer in the cytosol, and crosses the nuclear membrane.…”
Section: Introductionmentioning
confidence: 99%